Isolasi Fungi Tanah Muara Mangrove Desa Katialada Gorontalo dan Skrining Aktivitas Antibakteri terhadap Pseudomonas aeruginosa - Arthur Hariyanto Prakoso; Muhammad Zainul Arifin; Saeful Akhmad Tauladani; Gani Asri Muharam; Asia Asia; Ari Satia Nugraha (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2023)
Pseudomonas aeruginosa is a bacterial pathogen that causes various kinds of infections. The use of antibiotics is usually done to treat the infection. However, Pseudomonas aeruginosa has various resistance abilities that can avoid the efficacy of antibiotics. The emergence of drug resistance events encourages the need for the discovery of new antibiotic drugs, one of which comes from fungals secondary metabolite. Soil fungi from mangrove ecosystems have not been studied much. Interestingly, these soil fungi have unique adaptive responses. This response also affects the secondary metabolites it contains. Knowing this information, mangrove soil samples were cultured on fungi media which were then tested against Pseudomonas aeruginosa through antagonist test and microdilution test. Three fungal cultures with yeast characteristics were obtained and each of the secondary metabolite ethyl acetate extracts of these three fungi had antibacterial activity. The antibacterial activity was indicated by the % inhibition parameter. The terpenoid content in fungal cultures may be responsible for the antibacterial activity against Pseudomonas aeruginosa. This research is an initial screening of the search for new antibiotic candidates, so further research study such as isolation and species determination needs to be done.